Sprachkontaktinduzierte Grammatikalisierung am Beispiel des polnischen und kaschubischen Tempussystems - Bartelik, Piotr (Studia Germanica Posnaniensia, 2019)
This paper investigates various aspects of grammaticalization of Polish and Kashubian periphrastic verb forms with mieć\miec and bëc and participles. The involvement of factors, which are due to language contact or to autonomous development is thoroughly explored and analyzed in the context of basic grammaticalization parameters. At the same time this contribution should prove with valid arguments the thesis of an inhomogeneous, variably realized and partly of others (all above pragmatic) factors dependent grammaticalization der habere-\esse-forms in the Slavia. So this paper refers both to the canonical differences in the realization of single grammaticalization parameters as well as broader developmental tendencies in the Slavia.